Elevated expression of growth-regulated oncogene-alpha in tumor and stromal cells predicts unfavorable prognosis in pancreatic cancer. Issue 30 (July 2016) - Lian, Shuijin; Zhai, Xiaolu; Wang, Xudong; Zhu, Huijun; Zhang, Shu; Wang, Wei; Wang, Zhiwei; Huang, Jianfei
Abstract : Abstract: Growth-regulated oncogene-alpha (GRO-α) has been reported to be over-expressed in a series of human cancers including colorectal cancer, melanoma, gastric cancer, hepatocellular carcinoma, and ovarian cancer and was known to regulate multiple biologic activities associated with tumor progression. But the role in human pancreatic cancer remains unclear. To examine the expression of GRO-α and its clinical significance in pancreatic cancer (PC), a total of 12 fresh PC specimens and 12 surrounding normal tissues to detect GRO-α mRNA expression were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Immunohistochemical analysis of GRO-α protein was performed in 160 formalin-fixed, paraffin-embedded PC tissue samples and 68 control specimens, including 37 matched normal surgical margins and 31 benign pancreatic lesions. Kaplan–Meier survival and Cox regression analyses were performed to evaluate the prognosis of PC patients. Expression of GRO-α mRNA in PC tissues was significantly compared with that in adjacent normal tissues (1.399 ± 0.165 vs. 0.870 ± 0.103 t = 1.75, P = 0.012), GRO-α protein expression in cytoplasm of cancer cells and stroma was detected in 41.88% and 40.63% PC specimens, respectively, and was significantly higher than that in corresponding normal tissues ( P = 0.008, P = 0.002, respectively). High GRO-α expression in the cytoplasm of cancer cells was related to tumor location ( P = 0.047), tumor status (T classification; P = 0.001), distant metastasis ( P < 0.001), and tumor node metastasis (TNM) stage ( P < 0.001). High GRO-α expression in the stroma correlated with perineural invasion ( P = 0.010), T classification ( P = 0.006) and TNM stage ( P = 0.004), and was marginally associated with metastasis ( P = 0.056). Elevated expression of GRO-α in cytoplasm of cancer cells (hazard ratio [HR] = 5.730, P = 0.007) and stroma (HR = 3.120, P = 0.022) were independent prognostic factors of pancreatic cancer. T classification (HR = 2.130, P = 0.023), lymphatic metastasis (HR = 4.211, P = 0.009) and TNM classification (HR = 0.481, P = 0.031) were also prognostic predictors in PC patients. GRO-α expression was elevated in pancreatic cancer tissues and might be a potential therapeutic target and prognostic marker in patients with pancreatic cancer.